2010
DOI: 10.1677/erc-10-0234
|View full text |Cite
|
Sign up to set email alerts
|

AZD1152 negatively affects the growth of anaplastic thyroid carcinoma cells and enhances the effects of oncolytic virus dl922-947

Abstract: Novel therapeutic approaches are required for the treatment of anaplastic thyroid carcinoma (ATC), an incurable disease resistant to current available therapies. Aurora B is an important mitotic kinase involved in chromosome segregation and cytokinesis. It is overexpressed in many cancers including ATC and represents a potential target for chemotherapy. The effects of AZD1152, a specific Aurora B kinase inhibitor, have been evaluated against ATC, showing G 2 /M accumulation, polyploidy and subsequent cell deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 42 publications
8
44
0
Order By: Relevance
“…However, the treatment with the caspase inhibitor zVAD-fmk was not able to restore cell proliferation, supporting the involvement of other cell death pathways rather than the classical apoptosis. Our results are in agreement with the previous reports suggesting alternative cell death mechanisms induced by dl922-947 (Abou El Hassan et al 2004, Baird et al 2008, Libertini et al 2011.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, the treatment with the caspase inhibitor zVAD-fmk was not able to restore cell proliferation, supporting the involvement of other cell death pathways rather than the classical apoptosis. Our results are in agreement with the previous reports suggesting alternative cell death mechanisms induced by dl922-947 (Abou El Hassan et al 2004, Baird et al 2008, Libertini et al 2011.…”
Section: Discussionsupporting
confidence: 94%
“…It has been proposed that drugs blocking cells in G2 phase could enhance the effects of OVs. Indeed, we have demonstrated that the inhibitor of the mitotic kinase Aurora B, AZD1152, enhances the effects of dl922-947 by inducing a G2 arrest (Libertini et al 2011). Accordingly, the accumulation in G2 phase induced by radiation likely enhances the cytopathic effects of dl922-947.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To the best of our knowledge, only one paper has been published reporting the effects of AZD1152 in three of the ATC cell lines evaluated in this study, i.e. CAL62, BHT-101, and 8505C (Libertini et al 2011), and no reports are available on the effects of MLN8237 on ATC cells. The IC 50 obtained by Libertini and colleagues for CAL-62 and 8505C are similar to those calculated by us, while the IC 50 of BHT-101 is significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…Adeno 82,83 measles, 69 herpes simplex, 84,85 and vaccinia viruses 86,87 have been tested in vitro as well as in vivo in mouse explant models (Table 3). Conditionally replicative viruses include those that target cells with specific tumor suppressor pathways that have been [88][89][90] or are directed to negatively impact tumor growth such as targeting of angiogenesis.…”
Section: Preclinical and Clinical Studies Evaluating Potential Therapiesmentioning
confidence: 99%